Divergence of Financial Literacy Regulations and Imperatives: A Comparative Analysis of Indonesian and Malaysian Online Loans - Syamsuri, Andi Santri; Afdhal, Afdhal (Bacarita Law Journal, 2025)
The study presents a comparative analysis of online lending regulatory models in Indonesia and Malaysia, highlighting the crucial challenges in balancing rapid financial inclusion with strong consumer protection in the digital age. This study uses qualitative-comparative and empirical legal analysis approaches. This methodology includes testing policy frameworks and analysis of regulatory documents from the Financial Services Authority (OJK), Bank Negara Malaysia (BNM), and Securities Commission Malaysia (SC). The empirical approach is based on findings from a financial literacy education program involving 30 participants in Indonesia, whose effectiveness was measured through pre-test and post-test. The results show that the inclusive model in Indonesia, despite successfully expanding access, is struggling to face the massive proliferation of OJK eradicating 2,930 illegal online loans that cause significant financial losses of 3.4 trillion and erode public trust. In contrast, a conservative and segmented approach in Malaysia, by explicitly banning peer-to-peer (P2P) lending to individuals and directing digital finance to productive sectors, has effectively prevented the problem of widespread illegal lending. In conclusion, regulatory philosophy strongly shapes market outcomes and systemic risks. It emphasizes that proactive and preventive regulatory design is more effective than reactive law enforcement. As a suggestion, it is recommended that the development of a holistic regulatory strategy and the improvement of financial literacy be a national priority for Indonesia, as well as maintaining a conservative approach that has proven successful in Malaysia.